The ebook Elementary Calculus is based on material originally written by H.J. Keisler. For more information please read the copyright pages.


Example 3 (Continued)

We have 08_exp-log_functions-465.gif

One might recognize a3 + 3x2 + 3x + 1 at once as (x + 1)3. Alternatively, one can see easily that a = -1 is a root of x3 + 3x2 + 3x + 1. Therefore x + 1 is a factor of it. Dividing by x + 1 we get the quotient x2 + 2x + 1 = (a + 1)2.

The sum of partial fractions has the form

08_exp-log_functions-466.gif

Then

08_exp-log_functions-467.gif

Solving these three equations for A, B, and C we have A = 1, B = -2, C = 1.

Therefore 08_exp-log_functions-468.gif


Last Update: 2006-11-15